2004
DOI: 10.1007/s00428-004-1070-9
|View full text |Cite
|
Sign up to set email alerts
|

Array comparative genomic hybridisation analysis of gamma-irradiated human thyrocytes

Abstract: The susceptibility of thyroid epithelium to radiation-induced carcinogenesis is well recognised. In this context, thyroid carcinogenesis is associated with specific somatic ret/papillary thyroid carcinoma (PTC) rearrangements and morphologically with the papillary phenotype. Previous studies have demonstrated the possibility of inducing ret rearrangements in vitro using X-rays. The purpose of our study was to assess whether gamma (gamma) radiation using a Caesium 137 source can induce specific ret rearrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…To our knowledge, this represents the first array CGH study on PTCs, which includes post-Chernobyl thyroid tumours. We report Finn et al, 2004;Richter et al, 2004). The similarity in the results from conventional and array CGH demonstrates the reliability of the array CGH approach we used.…”
Section: Discussionmentioning
confidence: 60%
“…To our knowledge, this represents the first array CGH study on PTCs, which includes post-Chernobyl thyroid tumours. We report Finn et al, 2004;Richter et al, 2004). The similarity in the results from conventional and array CGH demonstrates the reliability of the array CGH approach we used.…”
Section: Discussionmentioning
confidence: 60%
“…A recently published CGH study concluded that, in particular, DNA gains in post-Chernobyl thyroid cancers appeared to be influenced by radiation exposure (28), which should have an impact at the transcription level. Another group demonstrated the possibility of inducing RET rearrangement in vitro using X rays (29). Using array CGH, they detected a predominant pattern of…”
Section: Discussionmentioning
confidence: 99%
“…16 In that report, the authors described using array CGH in cultured g-irradiated human thyrocytes to examine the molecular events that occurred in the postradiation setting. The study describes extensive copy number changes at multiple loci at specific spots in the genome.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular changes in this population are much less well studied. In an in vitro model of radiation-induced thyroid carcinogenesis, Finn et al 16 used array comparative genomic hybridization (CGH) to study copy number changes in the genome of cultured irradiated rat thyrocytes. They documented a variety of gains and losses across the genome in fairly consistent and specific sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation